THE DEVELOPMENT OF MODERN LOW TEMPERATURE FUEL CELLS - Andrzej Kowal; Dragica Chamovska; Milovan Jotanovic; Maciej Kopczyk (Journal of Engineering & Processing Management, 2012)
Classification of fuel cells is presented. Progress in low temperature fuel cells fueled by hydrogen, methanol and formic acid is discussed and the possible future use of fuel cells is indicated. Ethanol is a special fuel because it is available from renewable environmentally friendly sources and its oxidation product (CO2) can be transformed by photosynthesis to ethanol. The design of the anode catalyst for electrochemical ethanol oxidation in the Direct Ethanol Fuel Cell (DEFC) is described in some detail.
Keywords: low temperature fuel cel; anode catalyst; Direct ethanol fuel cel